Epidemiological Investigation of Salmonella Tilene by Pulsed-Field Gel Electrophoresis and Polymerase Chain Reaction - Chandar M Anand; Kevin Fonseca; Ken Longmore; Robert Rennie; Linda Chui; Mike Lingley; David Woodward (Canadian Journal of Infectious Diseases)
Pulsed-field gel electrophoresis (PFGE) and DNA fingerprinting by the polymerase chain reaction (PCR) were performed on 11 isolates of Salmonella tilene. Five strains were from a cluster of human patients, six from sugar gliders and pygmy hedgehogs kept as family pets or from local pet retailers, and one isolate from the first North American case of S tilene described in Washington State in 1994. The PFGE restriction patterns showed all isolates to be similar. However, PCR using primers to the 16S and 23S rRNA genes of Escherichia coli demonstrated that the Washington State isolate differed from the rest of the other isolates, which were all similar based upon their DNA fingerprint. This study indicates that reliance on one technique alone may be insufficient to show nuances between strains that are, in many respects, closely related.